Risk factors and a 3-month risk score for predicting pacemaker implantation in patients with atrial fibrillations. Issue 1 (24th March 2020) - Dalgaard, Frederik; Pallisgaard, Jannik Langtved; Lindhardt, Tommi Bo; Gislason, Gunnar; Blanche, Paul; Torp-Pedersen, Christian; Ruwald, Martin H
Abstract : Objectives: To identify risk factors and to develop a predictive risk score for pacemaker implantation in patients with atrial fibrillation (AF). Methods: Using Danish nationwide registries, patients with newly diagnosed AF from 2000 to 2014 were identified. Cox proportional-hazards regression computed HRs for risk factors of pacemaker implantation. A logistic regression was used to fit a prediction model for 3-month risk of pacemaker implantation and derived a risk score using 80% of the data and its predictive accuracy estimated using the remaining 20%. Results: Among 155 934 AF patients included, the median age (IQR) was 75 (65–83) and 51.3% were men. During a median follow-up time of 3.4 (1.2–5.0) years, 8348 (5.4%) patients received a pacemaker implantation. Risk factors of pacemaker implantation were (in order of highest risk first) age above 60 years, congenital heart disease, heart failure at age under 60 years, prior syncope, valvular AF, hypertension, ischaemic heart disease, male sex and diabetes mellitus. The derived risk score assigns points ranging from 1 to 14 to each of these risk factors. The 3-month risk of pacemaker implantation increased from 0.4% (95% CI: 0.2 to 0.8) at 1 point to 2.6% (95% CI: 1.9 to 3.6) at 18 points. Area under the receiver operator characteristics curve was 62.9 (95% CI: 60.3 to 65.5). Conclusion: We highlighted risk factors of pacemaker implantation in newly diagnosed AF patients and created a risk score. The clinical utility of the risk score needs further investigation.